On-farm economic and environmental impact of zero-tillage wheat: a case of north-west India - Aryal, Jeetendra Prakash; Sapkota, Tek Bahadur; Jat, Mangi Lal; Bishnoi, D.K. (Cambridge University Press, 2015)
Conducting farmers participatory field trials at 40 sites for 3 consecutive years in four rice-wheat system dominated districts of Haryana state of India, this paper tested the hypothesis that zero tillage (ZT) based crop production emits less greenhouse gases and yet provide adequate economic benefits to farmers compared to the conventional tillage (CT). In each farmer's field, ZT and CT based wheat production were compared side by side for three consecutive years from 2009–10 to 2011–12. In assessing the mitigation potential of ZT, we examined the differences in input use and crop management, especially those contributing to GHGs emissions, between ZT wheat and CT wheat. We employed Cool Farm Tool (CFT) to estimate emission of GHGs from various wheat production activities. In order to assess economic benefits, we examined the difference in input costs, net returns and cost-benefit analysis of wheat production under CT and ZT. Results show that farmers can save approximately USD 79 ha−1 in terms of total production costs and increase net revenue of about USD 97.5 ha−1 under ZT compared to CT. Similarly, benefit-cost ratio under ZT is 1.43 against 1.31 under CT. Our estimate shows that shifting from CT to ZT based wheat production reduces GHG emission by 1.5 Mg CO2-eq ha−1 season−1. Overall, ZT has both climate change mitigation and economic benefits, implying the win-win outcome of better agricultural practices.